PENERAPAN INTEGRATED VIDEO BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR EKONOMI MIKRO II - Dyah Perwita; Retno Widuri; Nur Choirul Afif (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to improve learning achievement in Microeconomics II courses through the application of integrated video-based learning. This research was conducted using a Classroom Action Research (CAR) approach through several stages that must be passed. The target of this research is the students of the Faculty of Economics and Business, Jenderal Sudirman University. Data collection techniques used are observation, interviews, tests and documentation. Based on the research that has been carried out in the first and second cycles, it can be said that there is an increase in learning achievement in Microeconomics II through the implementation of integrated video-based learning. The mastery of student learning outcomes in the Microeconomics II course using Integrated Video Based Learning increases. Student participation in Microeconomics lectures based on Integrated Video Based Learning increased from 14.2% to 18.3%